Trust and loyalty in building the brand relationship with the customer: Empirical analysis in a retail chain in northern Brazil - Antonio Cardoso; Marx Gabriel; Jorge Figueiredo; Isabel Oliveira; Reiville Rêgo; Rui Silva; Márcio José Sol Pereira Oliveira; Galv\~ao Meirinhos (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The purpose of this article is to analyze the relationship between a brand's trust in consumer decisions and its maintenance over time in a retail chain in northern Brazil known as Bemol. The sample consists of 210 respondents, customers of Bemol, and the methodology used is a model of structural equations. The developed model consists of 22 variables, divided into three constructs: trust, loyalty and brand. The results show the importance of trust in the consumption decision, as well as loyalty, relationship and satisfaction. Trust and loyalty lead to brand relationship, which is why managers must pay special attention to the factors to be provided to their customers so that this triad can be verified. Commercial brands marketed to the public should consider inducing strong feelings towards the brand as an important step in promoting customer satisfaction and loyalty. A brand for which that the consumer develops strong feelings will facilitate and potentiate positive behaviors in the long term. However, some behavioral characteristics, attendance and leadership, are of lesser importance to the consumer. This research presents a limitation as to its application, as the respondents were only customers of one brand, Bemol.
Keywords: 650; brand; customer; fidelity; loyalty; trust